Politics to the Extreme
XXVI, 246 p. 15 illus.
Keywords: To overcome the political deadlock that overshadows the pressing problems facing the United States, the academies top scholars address the causes and consequences of polarization in American politics, and suggest solutions for bridging the partisan divide.